Etude de la dépollution d’une eau chargée en métaux lourds - AOUDIA HANANE (My University, 2012)
The presence of heavy metals in a large number of rejection constitutes a major concern for the public autorities from the fatal conséquences bieng able to take place on the environment what makes their treatement imperative The objective set in this work is to evaluate the effectiveness of zéolithe Na-X and polymeric membranes containing « starch and bentonite with activated carbon addition » opposite the elimination of cadmium and lead.An experimental study of the influence of some parameters was carried in order to allow the optimisation of the retention of the both metals. The results of this study show that the both processes studied prove to be efficient ways opposite the depolltion of water charged of heavy metals.Zéolithe Na-X present satisfactory performance of retention for cadmium and lead compared to the polmeric membranes
Keywords: zeolithe,membrans,depollution,heavy metals